The Resiliency of Senior Teachers in Blended Learning - Policarpio, Janice M.; Lim, Rich Paulo Soriano (Akademika, 2025)
The COVID-19 pandemic necessitated an abrupt shift to blended learning (BL), exposing significant challenges for teachers, particularly senior educators perceived as vulnerable to technological demands. This study explored the resiliency of senior teachers in Angeles City, Philippines, who successfully implemented BL during the 2021–2022 school year. Using a qualitative multiple case study design, in-depth interviews were conducted with ten senior teachers (aged 51–61), all rated “Outstanding” in their performance. Findings revealed major challenges in online learning (technological hurdles, poor connectivity, low student motivation and attendance, difficulties in monitoring integrity) and offline modular learning (non-submission of modules, parental intervention, declining cooperation). Despite these obstacles, teachers displayed resilience through strategies such as continuous upskilling, flexibility in pedagogy, reward systems, strengthened home–school partnerships, optimized communication platforms, and interventions like home visits. Their coping mechanisms highlight passion, commitment, and adaptability. The study concludes that senior teachers are a resilient asset, “old but gold,” whose experiences offer valuable insights for educational policy and practice in times of crisis and beyond.